Republic of Armenia : Technical Assistance Report-Growth-Friendly Rebalancing of Taxes. (IMF Staff Country Reports; Country Report ;, 2019)
With the appointment of a new government, a lively debate has ensued about redirecting fiscal policies in support of a balanced revenue-raising strategy that is conducive to investment and growth. Currently, Armenia needs to raise more revenues in support of fiscal consolidation and to generate additional funding for developing and maintaining the physical infrastructure with special reference to the need of improving the urban built-up environment. Since the Authorities requested the mission to consider tax measures that are supportive of growth and/or tradeable sector, the proposed restructuring of taxes recognizes that real estate taxes, resource rent taxes, and broad-based consumption taxes (VAT and excises) are least distortive for growth. The 2016 Technical Assistance Mission in its report reviewed already unutilized tax bases as far as excises are concerned (taxation of gambling, mobile air time, waste packaging taxes, alcohol and tobacco taxation). As requested by the authorities, this mission focused on improving personal and business income taxes, presumptive taxation, and the recurrent real estate tax as base-broadening of the latter could support the fiscal program of the new government.